Analisis Kompetensi Guru Sejarah Kebudayaan Islam (SKI) dalam Melaksanakan Pembelajaran Kurikulum 2013 Berbasis Sistem Kredit Semester - Lesnida Lesnida; Zaini Dahlan; Siti Halimah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
This article aims to describe the results of the competency analysis of SKI teachers at MAN 2 Model Medan in implementing the 2013 curriculum learning based on the Semester Credit System. The method used is a qualitative research method with a naturalistic analysis approach using data collection techniques through observation, interviews and documentation. Then the data analysis techniques used through data reduction, data presentation and drawing conclusions. While the data validity techniques are credibility (trust), transferability (transferability), dependability (dependence), and confirmability (certainty). The results showed that: (1) The competence of SKI teachers in analyzing the characteristics of students was considered quite good, with indicators of understanding the physical, moral, spiritual, social, cultural, emotional and intellectual aspects of students. (2) The competence of SKI teachers in mastering learning theory and learning principles is quite good, with indicators of deep learning theory of constructivism, behaviorism, and cognitivism learning theory. While the learning principle uses the PAIKEM approach. (3) The competency of SKI teachers in implementing the 2013 curriculum based on credits is quite good, namely the implementation of learning using the 5 M approach, namely Associating, Asking, Observing, Creating networks, and Conducting trials. (4) The competence of SKI teachers in utilizing information and communication technology is in a good category, involving TV, films, VCD/DVD/VCR and the internet. (5) The competence of SKI teachers in using process evaluation and learning outcomes is quite good, with indicators of conducting an assessment taking into account the principles of continuity and authenticity including knowledge, attitudes and skills.